An Analysis Study on the al-Wâfi Bi Mâ Fî al-Shahihain by Shâlih Bin Ahmad Al-Syâmiy: Studi Analisis Terhadap Al-Wâfi Bi Mâ Fî Al-Shahihain Karya Shâlih Bin Ahmad Al-Syâmiy - Nurhaedi, Dadi; Daib Insan Labib, Muhammad Alfreda (Jurnal Living Hadis, 2023)
Al-Wāfî bimā fî Shahîhain li al-Imāmaini al-Bukhārî wa Muslim by Salih bin Ahmad al-Syāmî is a secondary-contemporary hadith book that is important to study. This book is unique compared to other similar books such as 'Umdah al-Ahkām by al-Maqdisi and al-Lu'lu' wa al-Marjān by Fuad Abdul Baqi. In this article, the issues studied in al-Wāfî are their position and significance, the systematization of the arrangement of hadiths and their books, as well as the method of selecting hadiths and summarizing their books. This problem is examined by comparative-confirmative analysis and analysis of its significance-relevance in the present context. The results of the study show that the book of al-Wāfî: (1) has a very important position because the theme is relatively complete, the hadiths are concise and representative, and the presentation of the book is easy, even though the themes and hadiths are limited; (2) the hadiths are arranged thematically, with a special systematic, detailed and easily accessible. However, for the current context, many new themes do not yet exist; and (3) the method of selecting the hadiths by standard is taking the most complete and representative hadiths, even though the implementation is sometimes inconsistent.